PRELIMINARY DESIGN OF GAS TURBINE WITH MULTI-SPOOL (CASE STUDY : M701F GAS TURBINE) - Syamsa Ramadan, Muhammad
Energy transition is of particular concern to the Indonesian government at the moment. Until 2023, the increase in PLN's power generation capacity has been dominated by an increase in the capacity of PLTGU and PLTG. Until 2022, the total generating capacity of PLTU and PLTGU reached 32.4% of PLN's total generation. So that gas turbines can be said to be an important component in electricity generation in Indonesia for the present and the future. This study begins by conducting parametric analyses for single-spool and multi-spool gas turbines. The design of the compressor and turbine is done using the mean-line design method. The combustion chamber design is conducted using zero-dimensional analysis. The turbine in the multi-spool consists of a gas turbine generator and a power turbine as a power generator. The design calculation results were validated with gas turbine on the field. The calculation results of the multi-spool design are compared with the single-spool to determine the effect of configuration changes. The results showed a net power of 398.44 MW, thermal efficiency of 45.67%, heat rate of 8530 kJ/kWh, flue gas temperature of 894.20 K, flue gas mass flow rate of 748 kg/s, compressor pressure ratio of 21, combustion chamber volume of 2.10 m3. The multi spool configuration gave a decrease in turbine outlet diameter 0.41 m with the same performance as single-spool gas turbine.